Trace metal concentrations in the offshore surficial sediment of the Heraklio Gulf (Crete Island, East Mediterranean Sea) - KOUKOUNARI, IOLI NIKOLETTA; PARASKEVOPOULOU, VASSILIKI; KARDITSA, AIKATERINI; KOULOURI, PANAYOTA; POULOS, SERAFEIM; DOUNAS, COSTAS; DASSENAKIS, MANOS (Mediterranean Marine Science, 2020)
The present study investigates the distribution of trace metals (Fe, Mn, Cr, Zn, Pb, Cu and Al), as indicators of pollution, in the surficial inner shelf sediments along the northern coast of Heraklio Gulf (Crete Island). Despite the fact that Heraklio Gulf is an industrialized urban area, hosting the third most important commercial harbour in Greece, the levels of trace metals in sediments are not exceedingly high. According to Sediment Quality Guidelines (SQG’s), the sediments are considered unpolluted with low probability of adverse effects to biota in the case of Cu, Zn and Pb, while moderately to heavily polluted only in the case of Cr. Moreover, Zn, Cu and Pb concentrations are lower than those measured in a previous study (1989). This improvement of environmental state in the study area is a response to more effective control of terrestrial pollution sources, following the enforcement of the Directive 91/271/EEC (as amended by Directive 98/15/EU) on urban wastewater treatment and disposal into Greek national legislation.